All-in-one care planning resource : medical-surgical, pediatric, maternity & psychiatric nursing care plans - Swearingen, Pamela L. (St. Louis, Missouri : Elsevier Mosby, 2012)
Provides 100 nursing care plans with the nursing diagnoses and interventions you need to know to care for patients in various clinical settings. This title includes care plans for pediatric, maternity, and psychiatric nursing in addition to medical-surgical nursing.
Part I: Medical-Surgical Nursing Care Plans General Care Plans -- Part II: Pediatric Nursing Care -- Part III: Maternity Nursing Care Plans -- Part IV: Psychiatric Nursing Care Plans
Includes bibliographical references and index.
Keywords: NURSING CARE PLANS